Study of Proportions Seaweed Eucheuma cottonii L. and Cooking Time on Quality of Functional of Seaweed Dodol - David Hermawan; Warkoyo Warkoyo; Claudia Jasmine; Okta Pringga Pakpahan (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
Seaweed as a source of nutrition contains carbohydrates, protein, lipid and ash. Ones of ingredients that works for healthy were dietary fiber. Eucheuma cottonii seaweed contains carrageenan, which can act as a stabilizer, a material thickening, gelling agent, and emulsifiers. This research is aim to know the level of resilience Dodol with the proportion of seaweed and cooking time. The study was conducted using a randomized block design consisting of two factors. The first factor is proportions seaweed thickener composition, glutinous rice flour, rice flour (30:35:30, 40:25:20, 50:15:10), the second factor is cooking time (20, 30, 40 minutes) repeated three times. The observations parameter includes moisture content, ash content, protein, lipid, crude fiber, and texture.The research results showed that has interaction between the proportion of seaweed and cooking time. The proportion of seaweed and cooking time gives effect to the moisture content and the texture of dodol seaweed. The proportions give effect to the moisture content, ash, lipid, crude fibre, and texture while treatment cooking time gives effect to the moisture content, ash, protein, lipid, and texture of dodol seaweed. The best treatment is produced by treatment of 50 g of seaweed: 15 g of glutinous rice: 10 g of rice flour and 40 minutes cooking time with the result 62.10% moisture content, 3.32% ash content, 2.42% protein, 3.25% lipid, 5.20% crude fibre, 76.70 N texture.